Sparkes, Rev. North River. Photograph of woman and little girl in house doorway. - Sparkes, Rev.
Photo of Evelyn Bradbury, daughter of James & Florence, and sister to Jean B Sparkes (Deaf Mute) & Elizabeth Bradbury